The Isles of Zetland [Showing] its Extent and Division into Parishes - Camden, William (Britannia: or, a Chorographical Description of the Flourishing Kingdoms of England, Scotland, and Ireland, and the Islands Adjacent, Vol. 4, 1806)
Map of Shetland, also called the Shetland Islands and formerly Zetland, a subarctic archipelago in the Northern Isles of Scotland situated in the Northern Atlantic between Great Britain, the Faroe Islands, and Norway.
Keywords: Great Britain; Travel; Voyages and travels; Maps; Scotland; Britannia (Camden, William); Islands; Scotland--Shetland